Clinical management and primary prevention of suspected coronary artery disease guided by computed tomography. Issue 9 (September 2021) - Beyer, Christoph; Birkl, Katharina; Feuchtner, Gudrun; Kofler, Lisa-Maria; Friedrich, Guy; Plank, Fabian
Abstract : Aims: Despite the well established role of coronary computed tomography angiography (CCTA) as a diagnostic gatekeeper, the yield of subsequent invasive coronary angiographies (ICA) remains low. We evaluated the adherence of CCTA integration in clinical management and primary prevention therapy. Methods: We retrospectively analyzed patients referred for ICA after CCTA without known coronary artery disease (CAD) or structural cardiac pathologies. Based on computed tomography (CT) findings, patients were classified as appropriately or inappropriately referred to ICA, equaling Coronary Artery Disease – Reporting and Data System (CAD-RADS) categories 0–2 (<50% stenosis) and 3–5 (>50% stenosis), respectively. CT exams were compared regarding invasive findings and revascularizations. Integration of CT results into primary prevention measures was analyzed and compared to measures taken after ICA. Results: Of 1005 patients referred for ICA, 81 (8.1%) had no obstructive CT findings and therefore no ICA indication. ICA inappropriate patients did not differ in symptom characteristics, but had a significantly lower revascularization rate (3.7% vs. 42.1%, P  < 0.0001) compared with patients appropriately referred to ICA. In patients with indication for lipid-lowering therapy after the CCTA statin rate was 53.1% and significantly increased after ICA to 76.4% ( P  < 0.0001). In CCTA, obstructive findings in proximal-only lesions did not increase the revascularization rate (45.6% vs. 42.1%, P  = 0.11) but missed nonproximal relevant stenoses (15.0% vs. 2.5%, P  < 0.0001) compared with obstructive findings in all segments. Conclusion: The overall rate of inappropriateness was low, but there is relevant statin underutilization in eligible patients due to a lack of CT findings integration. Both ICA referrals and primary preventive therapy could be improved by the implementation of CT results based on CAD-RADS recommendations.